2017
DOI: 10.1155/2017/7435657
|View full text |Cite
|
Sign up to set email alerts
|

Association between Parathyroid Hormone, 25 (OH) Vitamin D, and Chronic Kidney Disease: A Population-Based Study

Abstract: Identification of the accurate risk factor for CKD remains mandatory to combat the high prevalence of diseases. Growing evidence suggests the association of serum vitamin D with diverse health conditions. However, the relationship between vitamin D, intact parathyroid hormone (PTH), and calcium-phosphate metabolism and development of CKD remains controversial. We conduct this cross-sectional observational study to investigate the association between serum 25 (OH) vitamin D, intact PTH, and calcium and phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
1
12
0
1
Order By: Relevance
“…In our study, when adjusted for covariates, the lower eGFR values were significantly associated with increasing levels of 25(OH)D. Previous researchers have inves-tigated the relationship of 25(OH)D with eGFR, but results have been inconsistent (11)(12)(13)(14)(15)(16). The exact reasons for these discrepancies are unknown, but there are some explanations.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In our study, when adjusted for covariates, the lower eGFR values were significantly associated with increasing levels of 25(OH)D. Previous researchers have inves-tigated the relationship of 25(OH)D with eGFR, but results have been inconsistent (11)(12)(13)(14)(15)(16). The exact reasons for these discrepancies are unknown, but there are some explanations.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, the kidney has a critical role in the biosynthesis of 1,25(OH)2D even though there is no concordance regarding the relationship of the vitamin D concentrations with kidney function. Some studies demonstrated positive relationships between the 25(OH)D and the estimated GFR (eGFR) (11,12); others reported inverse associations (13,14); still others presented no associa-tion (15,16). These discrepancies may be due to differences in race, age, latitude and CKD status of the subjects.…”
mentioning
confidence: 99%
“…Out of which 126 (49.4%) were male and 129 (50.6%) were females with dominant female to male ratio 1. 20 Current study reveals the mean standard deviation of Alkaline phosphatase in three representative groups are 192.50±271.35, 178.61±124.20, 346.483±377.42 with highly most significant difference (<0.001).…”
Section: Resultsmentioning
confidence: 62%
“…Calcium (r = -0.23; p = 0.002), 24-hour urinary magnesium (r = -0.18; p = 0.020) and eGFR (r = -0.47; p = 0.001) showed a negative correlation with parathyroid hormone. [19][20][21], particularly musculoskeletal [22,23]. Secondary hyperparathyroidism can lead to bone loss due to increased bone turnover rates [24].…”
Section: Resultsmentioning
confidence: 99%